Analisis Metode Multi Factor Evaluation Process pada Pemilihan Produk Perbankan yang sesuai Kebutuhan Nasabah - Harmayani, H; Dwina, Vira (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2020)
PT Bank Negara Indonesia (Persero) Tbk is a business entity that collects funds from the public in the form of deposits. Based on the background of the problem, namely how to design and make a decision support system for selecting banking products according to customer needs in BNI using the multi-factor evaluation process method. The purpose of designing and making this decision support system is aimed at BNI customers or prospective customers in choosing the right deposit banking product as needed. In the process of opening an account at BNI, currently customer service is experiencing problems in the service time for opening an account which is getting longer. This is because the customer, when it comes to customer service, is still unable to determine which deposit product to choose, so customer service must explain all types of savings products at BNI. For this reason, the authors provide alternative solutions to problems by creating a decision support system for selecting banking products to the appropriate customer needs at BNI with the multi-factor evaluation process method. This decision support system is hoped to be able to help customer service at BNI so that the account opening process is faster and customers can get banking products that suit their needs without a long time.